Description of a large cohort of Caucasian patients with V122I ATTRv amyloidosis: Neurological and cardiological features. Issue 3 (29th May 2020) - Gentile, Luca; Di Bella, Gianluca; Minutoli, Fabio; Cucinotta, Francescopaolo; Obici, Laura; Mussinelli, Roberta; Arimatea, Ilenia; Russo, Massimo; Toscano, Antonio; Vita, Giuseppe; Mazzeo, Anna
Abstract: V122I is one of more than 130 mutations in transthyretin gene associated with hereditary TTR (ATTRv) amyloidosis. Main clinical expression is an infiltrative pseudohypertrophic cardiomyopathy with mild or no neurological symptoms. It is particularly common among African‐Americans (prevalence: 3%‐4%). We report 12 subjects from seven unrelated Caucasian families hailing from Sicily and carrying the V122I mutation. One patient was homozygous for V122I and in another family two subjects also carried the E89Q variant in compound heterozygosity. All the subjects underwent neurologic/neurophysiologic evaluation and cardiologic baseline tests; in five of them, cardiac magnetic resonance and/or (99 m) Tc‐DPD scintigraphy were performed. Three of 12 subjects were asymptomatic carriers. Of the remaining nine subjects, in four of nine patients, the nerve conduction studies revealed a polyneuropathy; in one of them, this represents the only sign of disease after 5 years of follow‐up. In eight of nine subjects, we found a hypertrophic restrictive cardiomyopathy and cardiac failure, associated with a carpal tunnel syndrome. Although in non‐Afro‐American individuals V122I prevalence is low, subjects carrying this mutation have been identified in the United Kingdom, Italy, and France. Our report describes a large cohort of V122I Caucasian patients from a non‐endemic area, confirming the possible underestimation of this mutation in the non‐African population. Moreover, it highlights the heterogeneity in the genotype‐phenotype correlation of ATTRv mutations, suggesting that the presence of a polyneuropathy has to be identified as soon as possible, since available treatments are, in Europe, so far authorized only for ATTRv amyloid peripheral neuropathy.